Growth, yield and nutrients of sweet cassava fertilized with zinc - Silva, Jessica Aparecida da [UNESP]; Leonel, Magali [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Garreto, Francisca Gyslane de Sousa [UNESP]; Nunes, Jason Geter da Silva [UNESP]; Tajra, Ricardo Figueiredo [UNESP] (Univ Federal Santa Maria, 2023)
The application of zinc fertilizers in the soil has been an agronomic practice to correct Zn deficiency in plants, aiming to increase productivity and/or nutritional quality. This study evaluated how zinc sulfate fertilization affects plant growth, yield performance and nutrient accumulation in the cassava 'IAC 576-70'. The experimental design was in randomized blocks with eight replications. The treatments consisted of 0, 1.5, 3.0, 4.5 and 6.0 g p1-1 ZnSO4. Results showed improvement in yield with soil fertilization with ZnSO4, with the optimal dose of 2.5 g pl-1. The uptake of nutrients in plant parts is favored with lower doses of zinc fertilizer, with maximum points ranging from 0.8 to 3.2 g pl-1 for macronutrients and 1.6 to 3.6 g pl-1 for micronutrients. The Zn content in tuberous roots increases by more than 40% with fertilization up to 2.8 g pl-1 of fertilizer, which contributes to the nutritional value of roots.
Keywords: Manihot esculenta; fertilization; minerals; biofortification